Effect of Epidermal Growth Factor on In Vitro Maturation, Fertilization and Early Embryonic Development of Cattle Oocytes - Baishya, Dipannita; Bora, Arundhati; Barman, Champak (International Journal of Bio-resource and Stress Management, 2024)
The present experiment was conducted during January, 2018 to March, 2019 in the laboratory, Dept. of Veterinary Physiology, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati, Assam (781022), India to investigate the effect of epidermal growth factor on in vitro maturation, fertilization and early embryonic development of cattle oocytes. A total of 318 nos. cattle ovaries were collected from slaughter houses for one year and 1089 nos. culturable oocytes were collected. 381 out of 1089 nos. culturable oocytes were subjected to EGF supplemented serum and serum free basic maturation media. The mean percentage of in-vitro maturation of cattle oocytes based on polar body extrusion was found to be significantly higher in EGF supplemented serum free basic maturation media (70.00±14.49) than the serum basic maturation media without EGF (54.17±7.19) respectively. But the mean percentages of in vitro maturation of cattle oocytes based on the cumulus expansion and polar body extrusion were found to be significantly higher in EGF supplemented serum free basic maturation media (77.59±5.48 and 70.00±14.49) than the value recorded in serum free basic maturation media without EGF (64.20±3.77 and 45.95±8.19). The mean cleavage percentages recorded at 4 cell, 8 cell, 16 cell and morula stages of embryos in EGF supplemented serum free culture media were found to be significantly higher than the value recorded in serum culture media without EGF. From the present experiment, it can be inferred that addition of EGF in serum free basic maturation media had little beneficial effect than serum basic maturation media.